As peculiaridades da Confederação Operária Brasileira (1906-1920) - Ribeiro, Alessandro Cardoso (2022)
This research represents the limits and actions coordinated by the Brazilian Workers' Confederation and its peculiarities within the Brazilian workers' movement during the First Republic. Idealized by intellectuals and workers 'leaders, this union central functioned as an agglutinating organ of the intellectuality that identified itself with the workers' cause, named by them as the social question. Thus, it is in this context that the organization of the Brazilian proletariat began, which, during this phase, counted on the leadership of libertarian immigrants, as well as Brazilian intellectuals from the urban middle classes, mainly on the Rio-São Paulo axis. However; given the different stages of industrial growth, and the composition of the working class itself, we find a diversity of workers 'movements, even under the direction of the Brazilian workers' confederation, of an anarcho-syndicalist nature. This important class organ, sought the transformation of the workers - named awareness by its creators - through three instruments: the lectures, the reading of the printed material produced (the newspaper A Voz do Trabalhador; the magazine A Vida; leaflets, among others) and workers' education, in rationalist schools. This same model was also followed by other workers' centers throughout Brazil. Founded in April 1906, during the first Brazilian workers 'congress, the Brazilian Workers' Confederation began to function effectively, from 1908, in the then capital of the country, in Rio de Janeiro. This union central sought to form, through its ideological devices, besides the so-called libertarian worker conscience, what they called a new anarchist man, that is, an archetype of a European libertarian model, totally alienated to our cultural condition, with a working class strongly marked by a counter- revolutionary moral economy and influenced by Christian religiosity, in its various aspects: Catholic, Protestant and Spiritist. Thus, although they realized that there was a cultural war within the process of class struggle, deconstructing these elements of the culture of the subordinate classes in the short term to make a revolution would be practically impossible, reducing in practice the workers' movement of the beginning of the First Republic to a purely reformist character, limiting the Brazilian Workers' Confederation only as a mediator of capital relations x work. The Brazilian Workers' Confederation functioned until 1918, but it continued to operate in a decentralized manner until 1920. During the 1930s, it was replaced by the Workers' Federation of São Paulo. The sources used were printed material published not only by the Brazilian Workers' Confederation (newspapers, magazines, books, among others), but also by some of the workers' centers affiliated to it, such as the Sergipe workers 'center, by the workers' federation of São Paulo, among others. The analysis procedures, on the other hand, were based on the theory of the English historian E, P. Thompson, covering a perspective, from a dialectical interrelationship among traditions, customs and social transformations, called by himself as peculiarities, contemplating not only the economic aspects within the historical process, but also cultural elements, going far beyond the old Marxist economic analysis, base-superstructure